Cytochrome P4502E1 inducibility and hydroxyethyl radical formation among alcoholics - Dupont, Isabelle; Lucas, Daniele; Clot, Paolo; Ménez, Catherine; Albano, Emanuele (Journal of hepatology, 1998)
Background/Aims: Animal studies have shown that the induction of cytochrome P4502E1 (CYP2E1) modulates oxidative damage induced by ethanol. Since CYP2E1 activity varies substantially in humans, we have investigated whether differences in CYP2E1 activity might influence the formation of hydroxyethyl free radicals and the stimulation of lipid peroxidation among alcohol abusers. Methods: Chlorzoxazone oxidation, an index of CYP2E1 activity, and the levels of antibodies reacting with hydroxyethyl radical and malonyldialdehyde protein adducts were investigated in 51 alcoholic patients. Results: We observed that in 40 out of 51 (78%) alcoholics, chlorzoxazone oxidation was increased over the control levels, consistently with CYP2E1 induction by ethanol. However, in the remaining 22% of the patients, in spite of a similar alcohol intake, chlorzoxazone oxidation was within the control range, indicating a lack of CYP2E1 inducibility. IgG reacting with hydroxyethyl free radical-protein adducts were absent in subjects without CYP2E1 induction, while they were significantly increased in alcoholics with induced CYP2E1 activity. IgG against malonyldialdehyde protein-adducts were increased in all patients, irrespective of CYP2E1 inducibility. Moreover, chlorzoxazone oxidation was significantly lower in alcoholics without clinical and biochemical signs of liver disease as compared to patients with alcoholic liver disease. Conclusions: These results indicate that CYP2E1 activity greatly influences the formation of hydroxyethyl radicals in humans, and suggest a possible role of CYP2E1 in the development of alcoholic liver disease.